Pengaruh Waktu Inokulasi terhadap Kejadian Penyakit Tular Benih Bean Common Mosaik Virus (BCMV) pada Tanaman Kacang Panjang (Vigna sinensis L.) - HANDAYANI, NI PUTU EKA; SUDANA, I MADE; NYANA, I DEWA NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.2, April 2017, 2017)
Influence of Inoculation Time Toward the Incidence of Bean Common Mosaic Virus (BCMV) Seed Borne Disease on Long Bean Plants (Vigna sinensis L.) This study aims to determine how far the influence of inoculation period of BCMV towards the incidence of seed borne diseases on long bean plants. This research activity includes planting of beans in the field, sampling on symptomatic plant mosaic; inoculation of BCMV mechanically, observation of symptoms, measurement of chlorophyll content, incidence of disease, calculation yields, percentage of germination test, percentage BCMV seed borne, ELISA serology test and data analysis. Design used was a randomized block design (RBD) with seven treatments and four replications. The results showed that long bean plants with 2 wap (weeks after planting) inoculation treatment indicates the variation of symptoms as diverse as heavy mosaic (Mb), malformation of leavs (Md), and dwarf (K). The chlorophyll content inoculation period 2 wap of 9.98 SPAD. Higher incidence of disease inoculation period 2 wap is 93%. The long bean plants that were infected by BCMV at 2 wap inoculation period resulted in yield average of 12.19 grams with the highest level of yield losses amounted to 95.52%. The grown seeds at 2 wap inoculation period had 0% germination.